Histopathological studies upon effects of zeranol on the reproductive system in male merino lambs - M. Kemal ÇİFTÇİ; Metin Münir KIRAN (Eurasian Journal of Veterinary Sciences)
Zeranal has been used as anabolic agent in cattle and sheep, especially in recent years. The purpose of this study was to determine the effects of zeranal on the development and histopathological changes of reproductive organs of male merino lambs implanted with zeranaL In this trial, tourty-five m ale merino lambs at 126 ± 8 days of age were used. These lambs were divided into three groups. Each group consisted of 15 animals. Group I and group II were implanted with 12 mg zeranal subcutaneously the base of ear of lambs at the baginning of trials. After that, the same dose of zeranal was reimplanted to group II 40 days after first implantation. The remaining 15 lambs were used as a control group. Five lambs from each groups were slaughtered at 80, 120 and 160 days atter the trial. The implantation of zeranal to the lambs induced histopathological changes in the genital tract, which included; reduced seminiferous tubular diameter, delayed spermatogenesis in the testes; increased interductal connective tissue, adenomyosis, hyperplasia and intraepithelial lumina in the epididymides; squamous metaplasia, cystic dilatation of same acini, keratinisation, hyperplasia and increase in connective tissue in the prestat and bulbourethral gland; reduced alveolar development and an increase in connective tissue, alveoler cystic dilatation in vesicular gland. lt may be concluded that zeranal induced changes in the testes was reversible, whereas changes in epididymides, prostat, bulbourethral and vesiculer gland were irreversible. For this reason, zeranal implanted lambs should not be used for breeding purpose.